2009
DOI: 10.1007/s10552-009-9351-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of metabolic syndrome with insulin-like growth factors among adults in the US

Abstract: These findings may prove useful to an understanding of the role of IGF-I in human disease, in particular its relation to metabolic syndrome, diabetes and potentially some cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
1
21
1
Order By: Relevance
“…The IGF1/IGFBP3 ratio was not associated with metabolic syndrome in our study. These findings in older men aged R70 years contrast with previously reported studies in younger and middleaged men (18,(25)(26)(27). In a report of 1463 younger men aged 20-49 years from the Third National Health and Nutrition Examination Survey (NHANES III), men in the lowest quartile of the IGF1/IGFBP3 ratio were three times more likely to meet the same definition of metabolic syndrome (18).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The IGF1/IGFBP3 ratio was not associated with metabolic syndrome in our study. These findings in older men aged R70 years contrast with previously reported studies in younger and middleaged men (18,(25)(26)(27). In a report of 1463 younger men aged 20-49 years from the Third National Health and Nutrition Examination Survey (NHANES III), men in the lowest quartile of the IGF1/IGFBP3 ratio were three times more likely to meet the same definition of metabolic syndrome (18).…”
Section: Discussioncontrasting
confidence: 64%
“…In a report of 1463 younger men aged 20-49 years from the Third National Health and Nutrition Examination Survey (NHANES III), men in the lowest quartile of the IGF1/IGFBP3 ratio were three times more likely to meet the same definition of metabolic syndrome (18). A separate analysis based on NHANES III data including men aged 50 years and above found that metabolic syndrome was associated with lower levels of IGF1 and a reduced ratio of IGF1/IGFBP3 (25). In a sample of 359 European men aged 30-64 years, IGF1 levels correlated inversely with fasting glucose, and were associated with lipid and obesity/glucose factors in a principal component analysis (26).…”
Section: Discussionmentioning
confidence: 99%
“…In cohorts with younger subjects investigating the relationship of IGF1 with the metabolic syndrome, the common finding is an association of low IGF1 concentrations and the metabolic syndrome (12,22,23). In cohorts with older subjects, the findings are more heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…In two previous studies on the association of IGF1 with the metabolic syndrome in older populations, U-shaped relationships have been reported (9,10). Others report low IGF1 values to be related to a greater metabolic burden (11,12,13,14). These cohort studies only speculate about the role of this association in the development of CVD over time.…”
Section: Introductionmentioning
confidence: 96%
“…In general patients with a low normal IGF-I who are obese and meet other criteria for metabolic syndrome tend to have a worse cardiovascular disease outcome than those with a mid to high normal IGF-I (50). Clearly many of these subjects have insulin resistance.…”
Section: Igf-i and The Metabolic Syndromementioning
confidence: 99%